1997
DOI: 10.1088/0953-4075/30/19/025
|View full text |Cite
|
Sign up to set email alerts
|

Drift and proton transfer reactions of positive ions in methane parent gas

Abstract: We have measured the mobility of , , and in methane over a wide range of the reduced field strength, E/N, from 15 to 520 Td with a drift-tube mass spectrometer. The mobility of the latter ion could be measured because of the presence of 200 ppm of water vapour in the gas, thus leading to the formation of by proton-transfer reactions between and with . A thorough measurement of the variation of the relative ionic fluxes of and with gas density, drift distance and E/N, allowed us to derive proton-transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The beam studies of Trepka and Neurt [6] and of Sharp and Dowell [7] on negative-ion formation in CH 4 show that the most abundant negative-ion species formed under their conditions were H − , followed by CH − 2 to a lesser, poorly defined extent. With regards to the positive ions, several species are formed either by electron-impact ionization or by ion-molecule reactions [11], as is the case for CH + 5 , C 2 H + 5 and C 3 H + 5 [10]. Also shown in figure 6 are the η/α values derived from the calculations of Bordage [3] and the ones measured by Hunter et al [4], a fair agreement between them is observed.…”
Section: Electron Attachmentsupporting
confidence: 53%
See 1 more Smart Citation
“…The beam studies of Trepka and Neurt [6] and of Sharp and Dowell [7] on negative-ion formation in CH 4 show that the most abundant negative-ion species formed under their conditions were H − , followed by CH − 2 to a lesser, poorly defined extent. With regards to the positive ions, several species are formed either by electron-impact ionization or by ion-molecule reactions [11], as is the case for CH + 5 , C 2 H + 5 and C 3 H + 5 [10]. Also shown in figure 6 are the η/α values derived from the calculations of Bordage [3] and the ones measured by Hunter et al [4], a fair agreement between them is observed.…”
Section: Electron Attachmentsupporting
confidence: 53%
“…The mean uncertainty in the measured values of this parameter is ±3-5% over the whole E/N range. Since it is very likely that, under the conditions of the present experiment, more than one positive-ion species is produced, either by electron impact or by secondary ionmolecule reactions [10,11], the lack of mass analysis in the present experiment leads us to regard our mobility values as the unresolved mean of more than one ion species drifting across the gap. To the best of our knowledge, no mobility data for daughter positive ions in methane above E/N = 560 Td have been published [10].…”
Section: Ion-drift Velocities and Mobilitiesmentioning
confidence: 91%
“…A needle is the most convenient form for igniting an electrical discharge; a metal ring is used to embed the needles in the structure of a sealed pipeline. The beads on the edges of the ring, facing into the air, serve to reduce the electric field in the air near the ring and prevent the ring from being coronated toward the air [4]. Figure 2 shows how the electrodes are positioned relative to each other and the pipe.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Methane discharge plasma can be treated as electropositive [9], so negative ions were not taken into account. For positive ion, the transport cross sections were taken to match the experimental results of ion mobility in methane [25,26]. Ion-ion and ion-electron collisions were not considered.…”
Section: Simulation Algorithmmentioning
confidence: 99%